HIGH GROWTH HORMONE LEVELS IN CLINICALLY SHORT STATURE CHILDREN - Awan, Tariq Mahmood; Sattar, Abdus; Khattak, Ihsan Gul (Journal of Ayub Medical College Abbottabad, 2006)
Background: Growth Hormone (GH) is secreted from the anterior pituitary gland. It binds to receptors on the surface of target cells, stimulates production of Insulin-like growth factor-I (IGFI) leading to growth of almost all tissues of the body capable of growing. Growth failure (height below 3rd centile) occurs in children who do not secrete sufficient amount of GH. In some children, however, short stature is present in the presence of high levels of GH in their blood and they also secrete normal to increased amounts of GH in response to stimulation tests when tested for possible deficiency of GH. This condition is known as GH resistance syndrome or Larons syndrome (LS). Methods: All patients after a thorough clinical evaluation underwent GH evaluation protocol as follows. On arrival in the lab a blood sample was collected for basal GH level in each patient. Screening was performed by subjecting the patients to exercise stimulation test and/or L-dopa stimulation test. Patients with GH deficiency underwent insulin tolerance test (ITT) after one week for confirmation. All the basal and post-stimulation samples were analyzed for GH levels. A level below 10mIU/L indicated GH deficiency, between 10-20mIU/L as borderline and an adequate response was defined as a GH >20mIU/L. Patients with a basal GH level of >20mIU/L and/or a post-stimulation level of >40mIU/L were arbitrarily considered as having exaggerated GH levels. This article evaluates the high plasma growth hormone levels among clinically short stature children undergoing growth hormone stimulation tests. Results: Two hundred ninty-three patients reported for GH evaluation. Twenty were excluded for various reasons. Thus 273 patients were included for GH evaluation out of which 66(24.2%) showed GH deficiency, 89(32.6%) were borderline while 118(43.2%) patients exhibited adequate response, with GH levels of >20mIU/L. A number of patients unexpectedly showed very high GH levels on screening tests. Out of 118 patients, 21 showed either very high basal levels of >20mIU/L and/or a much-exaggerated response to stimulation tests with levels more than about 40mIU/L. Close consanguinity was found in 67% of patients showing very high GH levels. Conclusion: Some children with idiopathic short stature may show high levels of GH during their evaluation for GH deficiency. We identified a considerable number of such patients. These patients require further investigations. KEY WORDS: Growth Hormone, Resistance Syndrome, Short Stature, Exercise, L-dopa, Insulin Tolerance Test (ITT).